Odpowiedź :
a)=4z²+12z+9-4z²+2z=14z+9
b)=(9s²+24s+16)-(4s²-8s+4)=9s²+24s+16-4s²+8s-4=5s²+32s+12
b)=(9s²+24s+16)-(4s²-8s+4)=9s²+24s+16-4s²+8s-4=5s²+32s+12
(2z + 3)<do kwadratu> - 4z<do kwadratu>+ 2z=
=4z+4z+6+9-16z+2z=-6z+15
(3s+4)<do kwadratu> - (2s-2)<do kwadratu> =
=9s+6s+8+16-4s-4s-4+4=7s+24
Zastosowałam wzory skróconego mnożenia.
=4z+4z+6+9-16z+2z=-6z+15
(3s+4)<do kwadratu> - (2s-2)<do kwadratu> =
=9s+6s+8+16-4s-4s-4+4=7s+24
Zastosowałam wzory skróconego mnożenia.
a) (2z + 3)^2 - 4z^2 + 2z = 4z^2 + 9 + 2*3*2z - 4z^2 + 2z = 9 + 14z
B) (3s + 4)^2 - (2s - 2)^2 = (3s^2 + 16 + 24s) - (4s^2 - 2*2*2s + 4)= 2s^2 + 16 + 24s - 4s^2 - 8s + 4 = - 2s^2 + 22 + 16s
B) (3s + 4)^2 - (2s - 2)^2 = (3s^2 + 16 + 24s) - (4s^2 - 2*2*2s + 4)= 2s^2 + 16 + 24s - 4s^2 - 8s + 4 = - 2s^2 + 22 + 16s